164k views
17 votes
6 1/6 6 1/3 6 2/3 6 3/2

6 1/6 6 1/3 6 2/3 6 3/2-example-1
User Bdhar
by
5.6k points

1 Answer

8 votes

Given:

The expression is


\sqrt{\sqrt[3]{6}}

To find:

The simplified form of the given expression.

Solution:

We have,


\sqrt{\sqrt[3]{6}}

Using the properties of radical and exponent, we get


=(\sqrt[3]{6})^{(1)/(2)}
[\because √(x)=x^{(1)/(2)}]


=\left(6^{(1)/(3)}\right)^{(1)/(2)}
[\because \sqrt[n]{x}=x^{(1)/(n)}]


=6^{(1)/(3)*(1)/(2)}
[\because (a^m)^n=a^(mn)]


=6^{(1)/(6)}

Therefore, the correct option is A.

User Vog
by
5.2k points